Pengaruh DPK dan NPL Terhadap ROA pada Sektor Perbankan yang Tercatat di BEI - Luis Figo Romario Hutahaean (Indonesian Journal of Economics and Management, 2021)
The purpose in this research was to find the effect of third party funds (DPK) and non-performing loans (NPL) on return on asset (ROA) at Banking Sector Listed On Indonesia Stock Exchange (BEI) period 2015-2019. The research sample was 30 companies using purposive sampling technique or sampling with severel considerations. The types of data used in this research is data panel The research method used is quantitative research. The analysis used to determine the effect of DPK and NPL on ROA is data panel regression with using Eviews 10 software. The results showed that the DPK partially had a negative and insignificant effect on ROA. The NPL partially has a negative and significant effect on Return On Assets (ROA). Meanwhile, simultaneously, DPK and NPL have a significant effect on ROA in banking companies listed on the Indonesia Stock Exchange in 2015-2019.